2006
DOI: 10.1161/01.hyp.0000218440.71846.db
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Function in Mice During Normal Pregnancy and in the Absence of Endothelial NO Synthase

Abstract: Abstract-In humans, the increased cardiovascular demands of pregnancy are met by increases in cardiac output (CO), stroke volume (SV), plasma volume (PV), and cardiac and aortic inner dimensions and a concurrent decrease in arterial pressure that indicates a fall in total peripheral vascular resistance. The mechanisms responsible for these changes are incompletely understood, but NO synthase (NOS) is believed to play a central role. We assessed whether C57Bl/6J (B6) mice show similar changes and whether these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
46
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(54 citation statements)
references
References 43 publications
8
46
0
Order By: Relevance
“…This result suggested that uterine vascular resistance was elevated in eNOS KO(ko) pregnancies. This result is consistent with lower uterine artery blood flows (Figures 1 and S1) and similar arterial blood pressures during pregnancy 7,8 in mice lacking the eNOS gene relative to WT controls.…”
Section: Reduced Uteroplacental Blood Flow and Elevated Uteroplacentasupporting
confidence: 85%
See 2 more Smart Citations
“…This result suggested that uterine vascular resistance was elevated in eNOS KO(ko) pregnancies. This result is consistent with lower uterine artery blood flows (Figures 1 and S1) and similar arterial blood pressures during pregnancy 7,8 in mice lacking the eNOS gene relative to WT controls.…”
Section: Reduced Uteroplacental Blood Flow and Elevated Uteroplacentasupporting
confidence: 85%
“…Despite considerable evidence implicating eNOS in preeclampsia, eNOS knockout (KO) mice do not develop the hallmark signs, gestational hypertension [7][8][9] or proteinuria. 9 Indeed, arterial pressure in eNOS KO mice decreases during pregnancy to become similar to that of pregnant wild-type controls.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…19 Mouse models have promoted understanding of mechanisms regulating gestational changes to the cardiovascular system. 20 Comparisons of micro-ultrasound measurements of placental growth and blood flow velocity between normal and mutant mice (i.e. Nos3 −/− ) revealed significant similarities to human pregnancies.…”
Section: Introductionmentioning
confidence: 96%
“…Nos3 −/− ) revealed significant similarities to human pregnancies. [20][21][22] Those mouse strains examined by micro-ultrasound have not lacked SA modification, a characteristic of mice deficient in uNK cells. This phenotype is reversible by transplantation of marrow genetically deficient for T and B cell differentiation (ie, NK+, T−B− marrow).…”
Section: Introductionmentioning
confidence: 99%